Referral letters to colorectal surgeons: the impact of peer-mediated feedback - Jiwa, Moyez; Walters, S.; Mathers, N. (Royal College of General Practitioners, 2004)
BACKGROUND: General practitioners (GPs) select few patients for specialist investigation. Having selected a patient, the GP writes a referral letter which serves primarily to convey concerns about the patient and offer background information. Referral letters to specialists sometimes provide an inadequate amount of information. The content of referral letters to colorectal surgeons can now be scored based on the views of GPs about the ideal content of referral letters. AIM: To determine if written feedback about the contents of GP referral letters mediated by local peers was acceptable to GPs and how this feedback influenced the content and variety of their referrals. DESIGN: A non-randomised control trial. SETTING: GPs in North Nottinghamshire. METHOD: In a controlled trial, 26 GPs were offered written feedback about the documented contents of their colorectal referral letters over 1 year. The feedback was designed and mediated by two nominated local GPs. The contents of referral letters were measured in the year before and 6 months after feedback. GPs were asked about the style of the feedback. The contents of referral letters and the proportion of patients with organic pathology were compared for the feedback GPs and other local GPs who could be identified as having used the same hospital for their referrals in the period before and after feedback. RESULTS: All GPs declared the method of feedback to be acceptable but raised concerns about their own performance, and some were upset by the experience. None withdrew from the project. There was a difference of 7.1 points (95% confidence interval = 1.9 to 12.2) in the content scores between the feedback group and the controls after adjusting for baseline differences between the groups. Of the GPs who referred to the same hospital before and after feedback, the feedback GPs referred more patients with organic pathology than other local colleagues. CONCLUSIONS: GPs welcome feedback about the details appearing on their referral letters, although peer comparisons may not always lead to changes in practice. However, in some cases feedback improves the content of GP referral letters and may also impact on the type of patients referred for investigation by specialists.